Pemenuhan Kewajiban Dan Tanggung Jawab Pemerintah Daerah Terhadap Hak Pendidikan Anak Di Kabupaten Bangka Selatan - Dewi, Virna; Rindiani, Anis; Yuliana, Sri; Pawari, Rahmianti Ranti (Universitas Sang Bumi Ruwa Jurai, 2024)
One of the principles of a rule of law is the principle of legality, which means that every government legal action must be based on applicable laws and regulations or every government legal action must be based on the authority granted by laws and regulations. By relying on the principle of legality, the government carries out various legal actions. Because every legal action implies the use of authority, it implies an obligation to be responsible. In accordance with the principle